Molecular Linkage Mapping and Marker-Trait Associations with NlRPT, a Downy Mildew Resistance Gene in Nicotiana langsdorffii - Zhang, Shouan; Gao, Muqiang; Zaitlin, David (Frontiers in Plant Science, 2012)
Nicotiana langsdorffii is one of two species of Nicotiana known to express an incompatible interaction with the oomycete Peronospora tabacina, the causal agent of tobacco blue mold disease. We previously showed that incompatibility is due to the hypersensitive response (HR), and plants expressing the HR are resistant to P. tabacina at all stages of growth. Resistance is due to a single dominant gene in N. langsdorffii accession S-4-4 that we have named NlRPT. In further characterizing this unique host-pathogen interaction, NlRPT has been placed on a preliminary genetic map of the N. langsdorffii genome. Allelic scores for five classes of DNA markers were determined for 90 progeny of a “modified backcross” involving two N. langsdorffii inbred lines and the related species N. forgetiana. All markers had an expected segregation ratio of 1:1, and were scored in a common format. The map was constructed with JoinMap 3.0, and loci showing excessive transmission distortion were removed. The linkage map consists of 266 molecular marker loci defined by 217 amplified fragment length polymorphisms (AFLPs), 26 simple-sequence repeats (SSR), 10 conserved orthologous sequence (COS) markers, nine inter-simple sequence repeat (ISSR) markers, and four target region amplification polymorphism (TRAP) markers arranged in 12 linkage groups with a combined length of 1062 cM. NlRPT is located on linkage group 3, flanked by four AFLP markers and one SSR. Regions of skewed segregation were detected on LGs 1, 5 and 9. Markers developed for N. langsdorffii are potentially useful genetic tools for other species in Nicotiana section Alatae, as well as in N. benthamiana. We also investigated whether AFLPs could be used to infer genetic relationships within N. langsdorffii and related species from section Alatae. A phenetic analysis of the AFLP data showed that there are two main lineages within N. langsdorffii, and that both contain populations expressing dominant resistance to P. tabacina.